Association of the CD59 and CD55 cell surface glycoproteins with other membrane molecules - Stefanová, I; Horejsí, V (Journal of immunology (Baltimore, Md., 1991)
mAb against human glycosyl-phosphatidylinositol-linked leucocyte surface Ag CD59 and CD55 immunoprecipitated from detergent lysates of HPB ALL cell line in addition to the respective Ag a common 80-kDa glycoprotein component and (glyco)lipids. The 80-kDa glycoprotein is different from otherwise similar CD44 Ag. The CD59 immunoprecipitate contained also a small amount of the CD55 glycoprotein and the CD55 immunoprecipitate minute amount of the CD59 Ag. These results are interpreted in terms of existence of noncovalent complexes resistant to dissociation by mild detergents and consisting of the 80-kDa glycoprotein, CD59 and CD55 glycoproteins, relatively tightly bound (glyco)lipids and possibly other so far unidentified components. These complexes contain probably also other glycosyl-phosphatidylinositol-linked Ag, as an anti-CD48 mAb immunoprecipitated also an apparently very similar complex. The complexes immunoprecipitated by mAb against the CD55, CD59, and CD48 Ag also contain a protein kinase activity. This type of complexes could not be demonstrated in several other cell types such as RBC, PBMC, and HeLa cells. However, a qualitatively very similar set of components was immunoprecipitated from the murine thymoma EL-4 cell line by an anti-Thy-1 mAb.
Keywords: CD59 Antigens; glykolipidy; membránové glykoproteiny; lidé; Glycosylphosphatidylinositols; molekulová hmotnost; CD antigeny; Humans; Membrane Lipids; Glycolipids; glykosylfosfatidylinositoly; Precipitin Tests; Molecular Weight; CD55 Antigens; membránové lipidy; Membrane Glycoproteins; antigeny CD59; Antigens, CD; precipitinové testy; receptory odpovědné za homing lymfocytů; Membrane Proteins; membránové proteiny; fosfatidylinositoly; Phosphatidylinositols; Receptors, Lymphocyte Homing; antigeny CD55